2013
DOI: 10.2967/jnumed.112.113654
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Amyloid Imaging Using 11C-PiB: Methodologic Considerations

Abstract: Several methods are in use for analyzing 11 C-Pittsburgh compound-B ( 11 C-PiB) data. The objective of this study was to identify the method of choice for measuring longitudinal changes in specific 11 C-PiB binding. Methods: Dynamic 90-min 11 C-PiB baseline and follow-up scans (interval, 30 6 5 mo) were obtained for 7 Alzheimer disease (AD) patients, 11 patients with mild cognitive impairment (MCI), and 11 healthy controls. Parametric images were generated using reference parametric mapping (RPM2), reference L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 28 publications
(38 reference statements)
8
139
4
1
Order By: Relevance
“…However, there were apparent reductions in amyloid plaque load in a subset of patients with lower baseline amyloid plaque load. In particular, as within subject variability in BP ND is less than 3% between two PET scans,21, 22 the three responder subjects in the 40 mg dose group are highly likely to have had significant reductions in brain amyloid plaque load during the study. We believe these reduction in brain amyloid plaque load are consistent with the scientific reports published during and after the conduct of the study that indicates neuronal p38 α through modulating autophagy‐lysosome protein degradation appears to play a “critical role” in amyloid beta generation and plaque production 28, 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were apparent reductions in amyloid plaque load in a subset of patients with lower baseline amyloid plaque load. In particular, as within subject variability in BP ND is less than 3% between two PET scans,21, 22 the three responder subjects in the 40 mg dose group are highly likely to have had significant reductions in brain amyloid plaque load during the study. We believe these reduction in brain amyloid plaque load are consistent with the scientific reports published during and after the conduct of the study that indicates neuronal p38 α through modulating autophagy‐lysosome protein degradation appears to play a “critical role” in amyloid beta generation and plaque production 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic amyloid PET scanning method of van Berckel and colleagues at the VU Medical Center was followed 21. In this method, dynamic emission scanning consists of 23 frames with progressive increases in frame duration (1 × 15 #bib3 × 5, 3 × 10, 2 × 30, 3 × 60, 2 × 150, 2 × 300, and 7 × 600 sec) for a total scan duration of 90 min followed by a full quantitative data analysis of the images.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, changes in rCBF do not appear to have a significant effect on DVR values estimated using nonlinear modeling or graphical analysis. 28 In summary, quasi-steady-state SUVR can be understood as a composite value consisting of an amyloid load-(specific binding) dependent component and a rCBF-dependent component. Though the rCBF-dependent component may be small it may anyhow influence longitudinal amyloid imaging by confounding estimates of the potential increase in amyloid plaque load when gradual changes in rCBF occur such as after clinical AD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Again, investigators have reported more robust and apparently less variable results from longitudinal analyses of distribution volume ratio than of SUVRs (5).…”
Section: See Page 1233mentioning
confidence: 99%